Bahasa Inggris - Pratiwi, Theodesia Lady (Study Program of English Literature, 2020)
Language cannot be separated from culture, thereby, learning a language must involve learning its culture. Course books as one of the elements of English Language Teaching (ELT) can be one of the media to accommodate cultures. This study is a qualitative content analysis which specifies on summative content analysis. Two series of English course books were selected by employing purposive sampling, namely When English Rings a Bell (WERB) and Bright. Three units in each course books were selected by employing systematic random sampling. The results show that culture in WERB and Bright is represented in the form of source culture, target culture, and international culture. WERB and Bright mostly represent the source culture. This study argues that the high representation of source culture is affected by the adoption of 2013 curriculum syllabus to build students’ identity. Although the target culture and international culture is very lowly represented, it may provide some opportunities for the students, especially for Junior High School Students, to start building their cultural awareness and intercultural competence.